2011
DOI: 10.1111/j.1469-8986.2011.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal activity reliably captures physiological differences between wins and losses during gambling on electronic machines

Abstract: Differential patterns of physiological arousal to win and loss events during gambling is central to psychological conceptualizations of gambling behaviors but is poorly researched. We recorded heart rate (HR) and skin conductance responses (SCRs) to wins and losses while 23 healthy participants played for small incentives on a simulated electronic gambling task. Wins produced large SCRs whereas losses did not, and large wins produced larger SCRs than small wins. Electrodermal measures also correlated with rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 80 publications
8
44
2
2
Order By: Relevance
“…The results of the present research are coherent with other gambling studies that suggest that achieving the prize is necessary to maintain a high the psychophysiological arousal during it (Coventry & Hudson, 2001;Lole, et al, 2012), but that having the expectation of being able to win the prize is more relevant than winning it (Ladouceur, Sévigny, Blaszczynski, O'Connor, & Lavoie, 2003;Wulfert, Roland, Hartley, Wang, & Franco, 2005). According to the design of the present research, gamblers showed this expectation in the first attempt, and especially in the betting and rotation of the roulette phases.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results of the present research are coherent with other gambling studies that suggest that achieving the prize is necessary to maintain a high the psychophysiological arousal during it (Coventry & Hudson, 2001;Lole, et al, 2012), but that having the expectation of being able to win the prize is more relevant than winning it (Ladouceur, Sévigny, Blaszczynski, O'Connor, & Lavoie, 2003;Wulfert, Roland, Hartley, Wang, & Franco, 2005). According to the design of the present research, gamblers showed this expectation in the first attempt, and especially in the betting and rotation of the roulette phases.…”
Section: Discussionsupporting
confidence: 81%
“…This is coherent with studies that suggest that electrodermal activity indices are more sensitive than heart rate to arousal changes in gambling studies (Crone, et al, 2004;Dawson, et al, 2011;Lole, et al, 2012;Miu, et al, 2008;Yucha, et al, 2007). On one hand, respect to skin conductance level it was evidenced that the arousal was higher in the betting phase than in the other two phases.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In real gambling, significant sums of money are wagered, won, and lost within a short period, whereas in previous laboratory-based studies (e.g., Lole et al, 2012;Wilkes et al, 2010), and the current study, rewards were capped and restricted to small amounts (movie voucher/s in the current study). Further, unlike real gambling, the participant does not suffer the risk of losing their own money, with losses often restricted to loss of free credits allocated to the research participant.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Wins were also associated with a clear phasic (Clark et al 2012(Clark et al , 2013Lole et al 2012;Dixon et al 2011), coupled with increased zygomaticus activity and decreased corrugator activity. While zygomaticus activity is a well-established response to appetitive stimuli such as erotic pictures, only two previous experiments have generalized this response to financial outcomes within a gambling context (Bediou et al 2011;Wu et al 2015).…”
Section: Winsmentioning
confidence: 99%